Opposition Resistance of the Nature Concerned Community Movement in Wadas Village (Equake Dewa) in Resisting Andesite Quarry Mining in Wadas Village, Purworejo Regency, Central Java - Angelina, Rica; Mar’iyah, Chusnul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Gerakan Masyarakat Peduli Alam Desa Wadas (Gempa Dewa) is here to reject andesite mining in their village. The reason for the rejection of Gempa Dewa was the loss of living space and residences that had been abandoned for a long time. On the other hand, there are also several accompanying reasons, namely environmental problems and the collective memory that the community has about the natural disaster that hit Wadas decades ago. The aim of this research is to analyze the opposition resistance carried out by Gempa Dewa in rejecting the andesite mining assistance in Wadas Village. This research uses qualitative research methods with data collection techniques, literature studies and documentation studies. Researchers used [1] data analysis techniques to obtain valid and comprehensive data. The results of this research were that it was found that several forms of oppositional resistance were carried out by Gempa Dewa in rejecting mining, including resistance through art, resistance with Mujahadah, and resistance by women's groups using symbols in their resistance. The hope is that with opposition resistance, the government will no longer use Wadas Village as an andesite mining location.